2013
DOI: 10.2217/rme.13.80
|View full text |Cite
|
Sign up to set email alerts
|

The Global Landscape of Stem Cell Clinical Trials

Abstract: The field is progressing at a steady pace with emerging business models for stem cell therapeutics. However, therapeutic rhetoric must be tempered to reflect current clinical and research realities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
98
0
4

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(103 citation statements)
references
References 34 publications
1
98
0
4
Order By: Relevance
“…However, the increasing of clinic trials based in MSC could let us understand better the effect of them in vivo and this will open new scenes to strengthen and valid clinic trials of medicine regenerative a great scale [65,[78][79][80][81]. This could be a solution by the world health problems that DM2, its complications and other kinds or disease do [82].…”
Section: Discussionmentioning
confidence: 99%
“…However, the increasing of clinic trials based in MSC could let us understand better the effect of them in vivo and this will open new scenes to strengthen and valid clinic trials of medicine regenerative a great scale [65,[78][79][80][81]. This could be a solution by the world health problems that DM2, its complications and other kinds or disease do [82].…”
Section: Discussionmentioning
confidence: 99%
“…To overcome these limitations, non-integrating adenovirus, sendai virus, episomal vector or completely DNAfree techniques have been developed [64][65][66][67], with the first in-human iPSC clinical trial taking place in 2014 [68]. The successful implantation of iPSC-derived retinal pigment epithelium cells into a patient with age-related macular dystrophy was reported; however, the trial was prematurely suspended when it was found that the second patient's differentiated cells contained multiple mutations [60].…”
Section: Induced Pscsmentioning
confidence: 99%
“…For example, referring to the current practice of using stem cells isolated from one tissue to treat disease or injury in a different tissue, the ISSCR's scare list states, "Thus, it is unlikely that a single cell type can be used to treat a multitude of unrelated diseases involving different tissues or organs" and "How and where the cells are put back into your body matters, and some clinics inject cells into places where they are not normally present and do not belong [2]." Yet, more than half of approved clinical trials are designed to evaluate just this hypothesis that stem cells may confer healing properties to heterologous tissues [5].…”
Section: Not So Different Treatmentsmentioning
confidence: 99%